THEORETICAL AND METHODOLOGICAL PRINCIPLES OF DEVELOPMENT OF CONVERGENT TECHNOLOGIES FOR SOLVING GLOBAL PROBLEMS - Matyushenko, Ihor (Social Economics, 2018)
The article is devoted to the study of the main trends of development of convergent technologies in the countries-technological leaders for solving global problems in the conditions of the new industrial revolution. The analysis and comparative characteristics of current economic paradigms aimed at solving global problems are given. It is established that the logic of the development of science moves from a narrow specialization to interdisciplinarity and the creation in the end of a unified science that synthesizes qualitatively new technical and social sciences. At the same time, there is a convergence of the sciences about man, nature and society, which leads to the emergence of a synergetic effect and creates theoretical bases for solving global problems. It is shown that with the advent of the first industry-wide NBIC technologies and sciences, mankind has received a new scientific and technological base that provides the opportunity: at the atomic-molecular level to control processes, synthesize artificial materials that do not exist in nature, and possess properties different from those existing in nature the nature of the substances; Model and program results using supercomputer and information technology; to receive a toolkit and a theoretical basis for the rapprochement of the organic world (living nature) with the inorganic due to the development of biotechnologies; describe and explain the processes in the human brain responsible for higher nervous activity, and implement these principles in artificial intelligence systems with the help of cognitive technologies. The main provisions of the modern concept of the convergence of knowledge, technology and society as a growing and transformationally interrelated interaction between technology, society and spheres of human activity are set forth in order to achieve mutual compatibility, synergy and interpenetration, to create added value and broader needs of humanity and achieve common goals. It is proved that the main trend in solving global problems of mankind on the basis of convergence of knowledge, technologies and society is the use of NBIC technologies as the core and fundamental tools for development and the spread of the Smart TEMP advanced production system as a key factor in the new industrial revolution.